Trashure as an ESG-Based Digital Innovation to Improve Community Welfare and Green Environment Sustainability - Vina Fauzia Kartika; Nur Azizah Wandinia Ghozali; Siti Anisa; Rahma Rina Wijayanti; Oryza Ardhiarisca; Siska Aprilia Oktaviani (Politeknik Ganesha Medan, 2025)
Waste management in Indonesia remains a critical challenge for suistainable development, exacerbated by population growth and changing consumption patterns. Data from Ministry of Environtment and Forestry (KLHK) in 2024 shows that only 59.94% of 33.7 million tons of annual waste in properly managed, with the rest polluting rivers or being burned. Jember Regency, for instance, faces low public awareness, inadequate infrastructure, and limited economic value from domestic waste. This Study aims to address these issues by developing TRASHURE, an ESG-Based digital platform managed by Badan Usaha Milik Desa (BUMDes), to transform waste into suistainable investments. Using the prototype method, the research iteratively designed a web application through rapid feedback cycles with BUMDes and rural communities. Key features include waste collection tracking, an educational module, a marketplace for recycled products,and suistainability accounting. The prototype process involved three iterations, refining usability and functionality based on user input. Result demonstrate that TRASHURE enchances community participation, reduces environmental pollution, and supports Suistainable Development Goals (SDGs), particularly Goals 12 (Responsible Consumption) and 13 (Climate Action).